Sustainable and Biomimetic Methodology for Extraction of High-Value-Added Compounds in Almond Hulls - Cremasco, Gabriela [UNESP]; Sutton, Adam T.; Funari, Cristiano S. [UNESP]; Arrua, Dario R.; Dussan, Kelly J. [UNESP]; Hilder, Emily F.; Bolzani, Vanderlan S. [UNESP]; Rinaldo, Daniel [UNESP] (MDPI, 2024)
Almond trees are the most cultivated nut tree in the world. The production of almonds generates large amounts of by-products, much of which goes unused. Herein, this study aimed to develop a green chemistry approach to identify and extract potentially valuable compounds from almond by-products. Initially, a screening was performed with 10 different Natural Deep Eutectic Solvents (NADESs). The mixture lactic acid/glycerol, with a molar ratio 1:1 (1:50 plant material to NADES (w/v) with 20% v/v of water) was identified as the best extraction solvent for catechin, caffeoylquinic acid, and condensed tannins in almond hulls. Subsequently, a method was optimized by a Design of Experiment (DoE) protocol using a miniaturized extraction technique, Microwave-Assisted Extraction (MAE), in conjunction with the chosen NADESs. The optimal conditions were found to be 70 °C with 15 min irradiation time. The optimal extraction conditions determined by the DoE were confirmed experimentally and compared to methods already established in the literature. With these conditions, the extraction of metabolites was 2.4 times higher, according to the increase in total peak area, than the established literature methods used. Additionally, by applying the multiparameter Analytical Greenness Metric (AGREE) and Green Analytical Process Index (GAPI) metrics, it was possible to conclude that the developed method was greener than the established literature methods as it includes various principles of green analytical chemistry.
Keywords: design of experiments; green chemistry; Microwave-Assisted Extraction; NADESs; Prunus dulcis